Antibody‐mediated rejection induced cardiogenic shock: Too late for conventional therapy. Issue 5 (30th April 2018) - Coutance, Guillaume; Van Aelst, Lucas; Hékimian, Guillaume; Vidal, Charles; Rouvier, Philippe; Saheb, Samir; Gautreau, Chantal; Leprince, Pascal; Varnous, Shaida
Abstract: Background: Data are scarce on the prognosis of heart allograft antibody‐mediated rejection (AMR) with cardiogenic shock (CS). Methods: We performed a retrospective, single center, observational study. We included patients with biopsy‐proven AMR and CS. We aimed to analyze the characteristics, treatment, and prognosis of patients treated for CS due to AMR. Patients alive after AMR were followed to analyze recurrences of AMR, graft function, and cardiac allograft vasculopathy (CAV). Results: Seventeen patients met the inclusion criteria. Patients were mostly males (70%). Median age at diagnosis was 56 years, and median time between heart transplantation and AMR was 21 months. AMR was mostly due to high‐level de novo class II DSA. Only 2 patients had past history of biopsy‐proven AMR. Despite aggressive immunosuppressive therapies, in‐hospital and 1‐year mortality were as high as 76% and 82%, respectively. Four patients were discharged from hospital. Two of them were diagnosed with recurrent subclinical AMR: one died suddenly and the other presented rapidly progressive CAV. Conclusion: CS due to AMR occurred mostly in patients without history of AMR who developed de novo class II DSA. Despite aggressive conventional immunosuppressive therapies, prognosis after CS due to AMR was poor.